Contamination of a milk bank pasteuriser causing a Pseudomonas aeruginosa outbreak in a neonatal intensive care unit. Issue 5 (1st September 2003) - Gras-Le Guen, C; Lepelletier, D; Debillon, T; Gournay, V; Espaze, E; Roze, J C
Abstract : An environmental investigation and a cohort study were carried out to analyse an outbreak of infection caused by a serotype O10 Pseudomonas aeruginosa in a neonatal intensive care unit. Thirty one cases of infection were recorded, including four lethal ones. The outbreak was stopped by eradicating the environmental sources: a contaminated milk bank pasteuriser and bottle warmer.